Planning and implementation of underground space in Chinese central business district (CBD): A case of Shanghai Hongqiao CBD. (January 2020) - Peng, Fang-Le; Qiao, Yong-Kang; Zhao, Jing-Wei; Liu, Kun; Li, Jia-Chuan
Highlights: Urban underground space (UUS) as a contributor to CBD development is analyzed. Necessity of UUS regulatory detailed planning in Chinese CBDs is explained. Framework of indicators and rules for UUS development regulation is set up. Imperative measures taken to guarantee the planning implementation are summarized. Implementation effects of UUS planning are quantitatively evaluated. Abstract: The increasing latent demand for underground space has been adequately considered in the planning process of the central business district (CBD) in Chinese cities. However, underground space plans in most of the Chinese CBDs have yielded few results because they are rarely realized in practice as envisioned. The roots of the problem can be traced back to the lack of effective planning approaches and, more importantly, the administrative management for planning implementation. In a broader sense, this also mirrors deeper deficiencies in the planning and administrative system for urban underground space in China. In this context, Shanghai Hongqiao CBD offers an exemplary case for other Chinese cities with respect to underground space planning and implementation in CBDs or other key areas. This paper presents in detail the entire process of underground space development in terms of planning and the implementation dimensions in the Core Area Phase I in Shanghai Hongqiao CBD, which is also applicable to other Chinese cities.